Local temporal Rac1-GTP nadirs and peaks restrict cell protrusions and retractions - Hu, Jianjiang; Gong, Xiaowei; Strömblad, Staffan (Karolinska Institutet, 2021)
Dataset used in the paper "Local temporal Rac1-GTP nadirs and peaks restrict cell protrusions and retractions".
The GTPase4.rar file contains the raw confocal images of HT1080 cell line stably expressing RhoA-2G or Rac-2G biosensors seeded on 6.9kPa polyacrylamid gel. Channel 1 and 2 are the FRET signals (excite 457nm, emission 482/35 nm and 525/50 nm). Channel 3 is the red fluorescent beads for the traction force calculation (by comparing to the corresponding cell free image file (containing "RL" in the file name)). Channel 4 is the transmission light for the cell morphology.
The Optogenetic.rar file contains the raw confocal images of HT1080 cell line stably expressing PA-Rac1(Q61L) or PA-Rac1(T17N) constructs perturbed by 488 nm light before and after 5 min imaging on the 6.9kPa polyacrylamide gel. Channel 1 is the PA-Rac1 constructs signal. Channel 2 is the far red fluorescent beads for the traction force calculation(by comparing to the corresponding cell free image file (containing "RL" in the file name)). The 3D collagen folder contains the representative raw confocal images of same stable HT1080 cell line seeded in the 3D collagen perturbed by 488 nm light before and after 5 min imaging.
The LLSM.rar file contains the representative lattice light sheet images of the HT1080 cell line stably expressing RhoA-2G or Rac1-2G biosensors seeded on the 6.9kPa polyacrylamide gel. The file is in .ims format which could be opened with Imaris software.
The WindowingResults.rar file contains the window sampled results from the GTPase4.rar and Optogenetic.rar.
The Codes.rar file contains the software and custom codes used in this study.
Keywords: Biochemistry and cell biology not elsewhere classified; Systems biology; Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi; Biochemistry; Biokemi